Dimethylammonium 2-amino-5-nitroterephthalate hemihydrate - Martin Krueger; Martin Albat; Florian Pieper; Norbert Stock (IUCrData, 2016)
The asymmetric unit of the title compound, C2H8N+·C8H5N2O6−·0.5H2O, comprises a monodeprotonated 2-amino-5-nitroterephthalate anion and a dimethylammonium counter-ion on general positions and a water molecule that lies on a twofold rotation axis. Extensive hydrogen bonding is observed between the carboxylate group and the dimethylammonium ion, the water molecule and the carboxylic acid group, as well as between the amino group, the water molecule and the carboxylic acid group (N—H...O and O—H...O hydrogen bonds are involved).